2003
DOI: 10.1002/zaac.200300053
|View full text |Cite
|
Sign up to set email alerts
|

The Combustion of SiCl4 in Hot O2/H2 Flames

Abstract: A simple kinetic model describing the molecular gas phase reactions during the formation of fumed silica (AEROSIL ) was developed. The focus was on the formation of molecular SiO 2 , starting from SiCl 4 , hydrogen and oxygen. Wherever available, kinetic and thermodynamic parameters were taken from the literature. All other parameters are based on quantum chemical calculations. From these data, an adiabatic model for the combustion reaction has been developed. It was found that a significant amount of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
(12 reference statements)
0
25
0
Order By: Relevance
“…Figure shows the contours of temperature and SiO 2 concentrations in the x‐z plane (at y = 0) for the cases that SiCl 4 is injected from the first layer nozzle, secondary layer nozzle and fourth layer nozzle, respectively. It is found that the effects of SiCl 4 injection position on flame temperature are small (see Figure A‐C) due to the small heat release from SiCl 4 combustion . However, great differences are found in the distributions of SiO 2 concentrations when particle formation is not considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the contours of temperature and SiO 2 concentrations in the x‐z plane (at y = 0) for the cases that SiCl 4 is injected from the first layer nozzle, secondary layer nozzle and fourth layer nozzle, respectively. It is found that the effects of SiCl 4 injection position on flame temperature are small (see Figure A‐C) due to the small heat release from SiCl 4 combustion . However, great differences are found in the distributions of SiO 2 concentrations when particle formation is not considered.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the effects of SiCl 4 injection position on flame temperature are small (see Figure 4A-C) due to the small heat release from SiCl 4 combustion. 12 However, great differences are found in the distributions of SiO 2 concentrations when particle formation is not considered. For the case that SiCl 4 is injected from the central nozzle (first layer nozzle), the generated SiO 2 monomers are primarily concentrated in the centerline near the burner inlet and a relatively large concentration gradient exists along the radial direction (see Figure 4D).…”
Section: Effects Of Sicl 4 Injection Positionmentioning
confidence: 99%
“…Detailed twenty-step oxy-hydrogen reaction mechanism from CHEMKIN model [13] plus reduced four-step SiCl 4 hydrolysis mechanism [10] is included in the volumetric reaction model, as listed in The radiative heat transfer, mainly contributed by gas-phase H 2 O, is solved by a Discrete Ordinate (DO) model [14], which solves the radiative transfer equation (RTE) for a finite number of discrete solid angles in the global Cartesian system. Each octant of the angular space is sectioned into two uniform extents in the polar and azimuthal angles respectively, and thus RTE in a total of 8 Â 2 Â 2 directions are solved in the whole angular space 4p.…”
Section: Turbulent Oxy-hydrogen Flame Modelingmentioning
confidence: 99%
“…Table 2 shows that the peak temperature is the highest under the condition of unity equivalence ratio, while the peak temperature is 300 K lower under fuel lean condition and 200 K lower under fuel rich condition. Note that the reduced fourstep SiCl 4 hydrolysis mechanism [10] somewhat overestimated the peak temperatures compared with the values experienced in industrial furnace, therefore more detailed mechanisms needs to be developed to accurately reproduce the temperature field in the future study. A broader yet uniform high-temperature region is of benefit for the synthesis of high purity silica since the temperature gradient is smaller in the top part of furnace, which is the main silica-formation region.…”
Section: Discrete Model and Gas-liquid Interactionmentioning
confidence: 99%
See 1 more Smart Citation